Menghadapi tantangan digital: Pendidikan karakter dan etika berinternet berdasarkan pancasila - Afrianti, Mike (Maliki Interdisciplinary Journal, 2025)
The purpose of this article is to study how the values contained in Pancasila can serve as a foundation for character education that teaches internet ethics and the importance of developing digital literacy. Pancasila-based character education is highly relevant in the digital era, especially in shaping responsible internet ethics. This article analyses each principle of Pancasila and demonstrates how these principles can be applied in the digital world to foster positive behaviour, respect diversity, and support social justice. Moreover, it is hoped that digital literacy based on Pancasila can teach the younger generation how to access, analyse, and use information wisely. Although its implementation is challenging, character education based on Pancasila combined with digital literacy can build an ethical and character-driven digital generation. This article emphasises that the government, schools, and society must work together to face these challenges in order to create an ethical and character-driven digital generation.